High Expression of FcγII (CD32) Receptor on Monocytes in Dengue Infected Patients - Umi Solekhah Intansari; Harina Salim; Usi Sukorini; Adika Zhulhi Arjana; Muhammad Juffrie (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Pathogenesis of severe dengue infection has not been elucidated. Immune complex of pre-existing antibodies and heterotypic dengue virus bind to FcγII (cluster of differentiation (CD32)) receptor (FcγIIR) on monocyte facilitates entry and replication of dengue virus. Aim of this study was to evaluate the expression of FcγIIR on monocytes in patients infected with dengue and in healthy subjects.METHODS: This study used a cross-sectional design that included patients infected with dengue who were hospitalized in Dr. Sardjito General Hospital, Panembahan Senopati Hospital, and Sleman Hospital, who met the inclusion criteria and selected consecutively. Examinations were completed using a lyse, no-wash method of flow cytometry. Computerized statistical analysis was conducted and was considered to be significant if p<0.05.RESULTS: Sixty-five study subjects were divided into healthy subjects (24 subjects) and patients with dengue infection (41 subjects). There were no significant differences in hemoglobin (Hb) and hematocrit (Hct) values between the groups, but differences were found in the number of leukocytes, absolute number of monocytes and platelet count (p<0.001, 0.002 and <0.001, respectively). The mean expression of FcγIIR monocytes in patients with dengue infection (208.77±32.06 median fluorescent intensity (MFI)) and the healthy subjects (124.03±47.76 MFI) with p<0.0001.CONCLUSION: The mean expression of FcγIIR monocytes in patients with dengue infection was higher than in healthy subjects.KEYWORDS: dengue infection, FcγII (CD32) receptor monocyte, flow cytometry